Effect of demonstration method on learning success - Philippe Tohon Loiser; Wanye Endne (Trigin Institute, 2022)
The purpose of teaching carried out in the classroom according to Mager is to focus on student behavior or performance as a type of out put that exists in students and can be observed and shows that these students have carried out learning activities. Thus the alternative hypothesis formulated has been able to know the truth in this research so that it can be taken as a conclusion from this study, namely that